Distribuição da energia no interior de uma estufa plástica no período inverno - Klar, Antonio Evaldo [UNESP]; Jadoski Jr., Cleber [UNESP]; Maggi, Marcio Furlan [UNESP]; Ramiro, Juliana [UNESP]; dos Santos, Alexandre Barreto Almeida [UNESP] (My University, 2006)
This work aimed to study the energy distribution in protected environment during the winter of 2005. A plastic tunnel (27.5 m long, 7.5 m wide, 3.2 m high in the center and 2.00 m high in both lateral sides) was covered with polyethylene 100 micra and black shadow screen (sombrite) in lateral sides at the FCA/UNESP, Botucatu - SP. 142 minievaporimeters (500 ml volume and 147 cm2 area) were evenly distributed and set up at three heights: 0.40 m; 0.80 m and 1.20 m from soil surface in order to analyze energy distribution along the studied area. The greenhouse longitudinal axis was northwest/southeast, based on true north. Geosatistics principles and the GS+ Program were adopted to compare variables. From obtained results, it was concluded that there were significant evaporation variations at different points anf heights; the highest values were the ones closest to the soil surface (0.40m) in July and at highest heights (0.80 and 1.20m). Highest evaporations occurred in the southeastern side of the greenhouse.
Energy distribution in a plastic tunnel in winter period
Keywords: Geostatistics; Greenhouse position; Microevaporimeters